2014
DOI: 10.1152/ajpheart.00166.2014
|View full text |Cite
|
Sign up to set email alerts
|

Gi proteins mediate activation of the canonical hedgehog pathway in the myocardium

Abstract: During myocardial ischemia, upregulation of the hedgehog (Hh) pathway promotes neovascularization and increases cardiomyocyte survival. The canonical Hh pathway activates a transcriptional program through the Gli family of transcription factors by derepression of the seven-transmembrane protein smoothened (Smo). The mechanisms linking Smo to Gli are complex and, in some cell types, involve coupling of Smo to Gi proteins. In the present study, we investigated, for the first time, the transcriptional response of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…As discussed in more detail below (46), this structural homology couples with the observation that activating mutations in Smo occur at sites that appear to stabilize the inactive state of class A GPCRs to suggest that the 7TM region of Smo is likely to undergo GPCR-like conformational changes during its activity cycle (45). Such a conformational cycle would also be consistent with the ability of Smo to signal through G-proteins in certain circumstances (47)(48)(49)(50)(51)(52).…”
Section: Smoothened: 7tm Regionmentioning
confidence: 64%
“…As discussed in more detail below (46), this structural homology couples with the observation that activating mutations in Smo occur at sites that appear to stabilize the inactive state of class A GPCRs to suggest that the 7TM region of Smo is likely to undergo GPCR-like conformational changes during its activity cycle (45). Such a conformational cycle would also be consistent with the ability of Smo to signal through G-proteins in certain circumstances (47)(48)(49)(50)(51)(52).…”
Section: Smoothened: 7tm Regionmentioning
confidence: 64%
“…In vitro data were confirmed in transgenic mice with cardiomyocyte-inducible GiCT expression [37]. Transgenic GiCT mice showed specific reduction of Gli1 expression in the heart under basal conditions and failed to upregulate the Hh pathway upon ischemia and reperfusion injury [37]. This study characterizes the transcriptional response of cardiomyocytes to Shh and establishes a critical role for Smo coupling to Gi in Hh signaling in the normal and ischemic myocardium.…”
Section: Hedgehog In the Ischemic Heartmentioning
confidence: 79%
“…In addition, neonatal rat ventricular cardiomyocytes infected with an adenovirus encoding GiCT, a peptide that impairs receptor-Gi protein coupling, showed reduced activation of Hh targets. In vitro data were confirmed in transgenic mice with cardiomyocyte-inducible GiCT expression [37]. Transgenic GiCT mice showed specific reduction of Gli1 expression in the heart under basal conditions and failed to upregulate the Hh pathway upon ischemia and reperfusion injury [37].…”
Section: Hedgehog In the Ischemic Heartmentioning
confidence: 95%
See 1 more Smart Citation
“…GLI-dependent and -independent Hh signaling coexist in cells that have primary cilia, mainly cells in interphase or quiescent, like cardiomyocytes. We previously reported that SMO/G i protein coupling mediates up-regulation of canonical Hh signaling in response to ischemia and reperfusion injury, using animals with Tet-Off controlled cardiomyocyte-specific expression of a G i inhibitory peptide (the C-terminal domain of the G␣ i2 subunit) (G i CT/TTA mice) (12,13). In addition, we found that SMO activation rapidly reduces cAMP levels elevated in response to ␤ 2 -adrenergic receptor stimulation with isoproterenol (ISO) in cardiomyocytes in a G i protein-depen-dent manner (12).…”
Section: Smo (Smoothened) the Central Transducer Of Hedgehog Signalimentioning
confidence: 99%